ChemInform Abstract: Properties and Reactivity of Gaseous Distonic Radical Ions with Aryl Radical Sites. Issue 46 (24th October 2013) - Williams, Peggy E.; Jankiewicz, Bartlomiej J.; Yang, Linan; Kenttamaa, Hilkka I.
Abstract Review: 329 refs.